DEVELOPING POP-UP BOOK OF CHEMICAL HOUSEHOLD TOPIC FOR JUNIOR HIGH SCHOOL LEVEL - Ghery Priscylio; Rini Fath Marsya; Latisma Latisma; Andromeda Andromeda (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2020)
This study aimed to develop pop up book on Chemical in Household topic. Method of the study used Research and Development by 4-D stages model; define,design,develop and disseminate. Validation sheet and practically questionnaire were the instrument to collect the data. The pop up book was validated by four experts, 2 lecturers from the Department of Chemistry, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 1 lecturer of FBS Fine Arts, Universitas Negeri Padang and 1 junior high school science teacher. The practicality of the instructional materials was carried out on 1 science teacher and 27 eighth grade students at SMP Negeri 21 Padang. The data obtained were analyzed by using Cohen Kappa Formula. The validity test of the Pop Up book obtained an average value of kappa 0.87 moment with a very high category and a practicality test for the book based on the results of data analysis from teachers’ and student questionnaires. The response of teachers’ questionnaires obtained a 0.89 kappa moment value with a very high practicality category. The response of students’ questionaires got an average moment value of kappa 0.83 with a very high practicality category. The result also showed that the Pop Up book can increase students' interest to learn and understand science lessons in junior high school level.